Strategi Kemasan Tari Lembu Tanon Berbasis Kearifan Lokal di Dusun Tanon - Harist Harjanti Wijaya Mulia Catur Tunggal; Widodo Widodo; Malarsih Malarsih (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The lembu tanon dance is a dance that represents the local wisdom values ​​of the people of Dusun Tanon. The purpose of this research is to analyze the value of the wisdom of the local community of Dusun Tanon which is represented in the lembu tanon dance performance. The method used is qualitative with an interdisciplinary approach. The results of the study show that the lembu tanon dance is a representation of the activities of the Tanon Hamlet community. This can be seen from the pattern of the lembu tanon dance performance, in the lembu tanon dance there are also local wisdom values ​​such as politeness, mutual cooperation and greeting. The implications of the research with the lembu tanon dance can be used as a dance that characterizes Dusun Tanon and used as a tour package.